Pelatihan Tajhizul jenazah untuk Membekali Keterampilan Praktis dalam Mengurus Jenazah - Aini, Ulfa Nur; Zahro, Siti Fatimatus; Idamaningati, Idamaningati; Sarif, Muhammad Maulana Alfin; Sa’djiyah, Siti Halimatuz; Sukma, Yasinta Nirani; Ikha’a, Anadza Awaenal; Muzaki, Mohammad Mufid; Rozaq, M. Akmalul; Ramadhani, Ahmad; Fawa’id,, Muhammad Wildan (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The Tajhizul jenazah training was held to equip the community with practical skills in managing corpses according to Islamic law, as a form of community service in Ngetrep Village. This activity aims to improve the understanding and skills of residents in carrying out the corpse handling procession which includes bathing, shrouding, praying, and burying. The service method used includes a participatory approach with theory sessions, practical demonstrations, and direct simulations under the guidance of a fiqh expert. The training, which was attended by 25 participants on Sunday, July 28, 2024, took place at the Ngetrep Village Hall. The results of the service showed a significant increase in the understanding and abilities of the participants, demonstrated through direct practice and evaluative discussions. In addition, this activity also builds collective awareness of the importance of tajhizul janaza skills as a form of social solidarity and religious obedience. This program is expected to contribute to the sustainability of independent community-based corpse management.